Translation and Psychometric Evaluation of the Chinese Version of the Mathematical Resilience Scale - Xia, Wang; Amalia, Madihie; San Nah, Sze (SSRN, 2025)
This study aims to translate the Mathematical Resilience Scale and assess its psychometric properties. The objective was to determine the validity and reliability of the Mathematical Resilience Scale in Chinese. Methods: The translation followed a back-to-back translation process, and validity was accessed through exploratory factor analysis and confirmatory factor analysis. A convenience sample of 681 participants was chosen to represent the population of Anhui, China, for testing reliability and validity. Results: The Cronbach's α value of the Mathematical Resilience Scale was .969, indicating excellent performance. Additionally, the items demonstrated strong factor loadings, ranging from .514 to .859., and the Kaiser-Meyer-Olkin value was .968. The correlations between scales ranged from .506 to .782. Conclusion: The Mathematical Resilience Scale has been accurately and thoroughly translated into the Chinese version of the Mathematical Resilience Scale, with high psychometric properties.